2020
DOI: 10.34117/bjdv6n5-510
|View full text |Cite
|
Sign up to set email alerts
|

Aproveitamento das cinzas de caroço de açaí na produção de concreto sustentável analisando sua durabilidade

Abstract: Aproveitamento das cinzas de caroço de açaí na produção de concreto sustentável analisando sua durabilidade Use of açaí stone ash in the production of sustainable concrete analyzing its durability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Even so, the material acted as a filler in the cement matrix and showed good mechanical performance when applied to the concrete. Do Nascimento et al [32] also applied ASA in concrete, and they observed that the addition of ash brought benefits to the durability of the compound, making it less inclined to carbonation due to the filler effect of ASA. Marins et al [4] studied the incorporation of ASA in structural ceramics and concluded that up to 15% of ash improved the physical and mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the material acted as a filler in the cement matrix and showed good mechanical performance when applied to the concrete. Do Nascimento et al [32] also applied ASA in concrete, and they observed that the addition of ash brought benefits to the durability of the compound, making it less inclined to carbonation due to the filler effect of ASA. Marins et al [4] studied the incorporation of ASA in structural ceramics and concluded that up to 15% of ash improved the physical and mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos estudos relataram que materiais de origem natural podem ser usados com bom potencial em compósitos cerâmicas a base de cimento (Onuaguluchi et al, 2016;Miller, 2018;Lima et al, 2020;Marques et al, 2019;Oliveira et al, 2020 ).…”
Section: Introductionunclassified